2013
DOI: 10.1111/hepr.12235
|View full text |Cite
|
Sign up to set email alerts
|

Oral l‐ornithine‐l‐aspartate in minimal hepatic encephalopathy: A randomized, double‐blind, placebo‐controlled trial

Abstract: A 60-day oral LOLA course was not better than placebo in treating MHE, but was useful in preventing further episodes of OHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 29 publications
(48 reference statements)
1
37
0
5
Order By: Relevance
“…2Forest plots indicating the pooled effect of LOLA versus placebo/no intervention for improvement of mental state in a all HE patients, b patients with OHE. Trials included: Kircheis et al [8], Stauch et al [9], Chen et al [10], Abid et al [12], Mittal et al [13], Alvares da Silva et al [14], Sidhu et al [15], Ahmad et al [16], Sharma et al [17]
Fig. 3Forest plots indicating the pooled effect of LOLA versus placebo/no intervention for improvement of mental state in patients with MHE a irrespective of the drug formulation of LOLA b using the oral formulation.
…”
Section: Systematic Reviews and Meta-analyses Of Published Rctsmentioning
confidence: 99%
“…2Forest plots indicating the pooled effect of LOLA versus placebo/no intervention for improvement of mental state in a all HE patients, b patients with OHE. Trials included: Kircheis et al [8], Stauch et al [9], Chen et al [10], Abid et al [12], Mittal et al [13], Alvares da Silva et al [14], Sidhu et al [15], Ahmad et al [16], Sharma et al [17]
Fig. 3Forest plots indicating the pooled effect of LOLA versus placebo/no intervention for improvement of mental state in patients with MHE a irrespective of the drug formulation of LOLA b using the oral formulation.
…”
Section: Systematic Reviews and Meta-analyses Of Published Rctsmentioning
confidence: 99%
“…It has been studied extensively with better results with its intravenous rather than oral formulation across the HE spectrum 79,80,81,82,83,84 .…”
Section: Management Of Che and Ohementioning
confidence: 99%
“…However, evidence for its use in mHE is conflicting, with one meta-analysis suggesting a beneficial effect but a randomised control trial suggesting that it had no effect, although the data also suggested that fewer patients progressed to overt HE compared to placebo [30,31]. …”
Section: Treatment Of Mhementioning
confidence: 99%